Media, Education and Islamophobia: The Representation of Islam and Muslims in Indonesian Media - Khoirotusyarifah; Ita Tahyudin; Faisal Anwar Husain; Erni Haryanti (al-Afkar, Journal For Islamic Studies, 2026)
This study was intended to depict what the role of education is in overcoming islamophobia in muslim communities by increasing awareness, critical thinking, and tolerance. There are two main reasons for this study, (a) media has become a boomerang in islamophobia, (b) lack of public awareness in digesting messages through social media so that it causes discrimination, prejudice, and hostility. This study was phenomenology approach of qualitative study. The findings reveal; (1) Education can create people more critical. (2) Institutions and schools can reduce bias and stereotypes through an inclusive curriculum that emphasizes human values. (3) Education can humanize humans. Further, islamophobia occurs in our society due to the fact that they consume information directly without re-checking whether the information is true or false. It can be conclude that the media as a power is also often a fire that makes people confused about which side they should consider right, therefore through education, the community can be invited to think critically.